Complexation Behaviour of Some 3d Metals Ions with Aminobenzoic Acids - Basak, Devashish (Asian Journal of Chemistry, 2010)
The formation of binary complexes of 2-aminobenzoic acid, 3-aminobenzoic acid and 4-aminobenzoic acid with Co(II), Nd(II), Cu(II) and Zn(II) has been studied electrophoretically at 25 ± 1ºC and constant ionic strength (μ═ 0.1 M HClO4) in aqueous medium. The stability order was found to be Cu(II) > Co(II) > Zn(II).